Geometrichem Game to Improve Students' Learning Autonomy in Molecular Shape Topic - Sanih Gholiyah; Achmad Lutfi (Journal of Educational Chemistry (JEC), 2021)
Learning media can help teachers to convey material to students. One of the learning media that can be used is the game. The aim of this research is to determine the feasibility of Geometrichem game as a learning medium to improve student learning autonomy in molecular shape topic according to validity, practicality, and effectiveness. Geometrichem game is expected to improve student learning autonomy. The research method applied was Research and Development: (1) preliminary study, (2) development of the product, (3) trial. The trial was conducted to 18 students of SMAN 1 Gresik. The result showed that Goemterichem game is feasible as a learning medium in molecular shape topic as (1) validity reached 89,29% or very valid, (2) practicality reached 84,03% or very practical according to response questionnaire, and 78,79% or good according to student activity observation, (3) effectiveness reached 77,78% according to classical completeness. Geometrichem game improved student learning autonomy in student motivation, the use of learning resources, self-evaluation, and environmental factor aspects, but not in learning strategy, planning, and self-monitoring aspects.